Soft-Template Construction of 3D Macroporous Polypyrrole Scaffolds - Liu, Shaohua; Wang, Faxing; Dong, Renhao; Zhang, Tao; Zhang, Jian; Zheng, Zhikun; Mai, Yiyong; Feng, Xinliang (Small, 2017)
Researchers demonstrate a bottom-up approach toward 3D hierarchical macroporous conducting polymer aerogels via soft template-directed synthesis and self-assembly of ultrathin polypyrrole (PPy) nanosheets in solution, involving that perfluorocarboxylic acids (PFCA) amphiphiles self-assemble into lamellas with a bilayer structure in ethanol/H2O solution, which guide the polymerization of pyrrole monomers into ultrathin PPy nanosheets. The further polymerization results in the cross-linking of the adjacent PPy nanosheets and establishment of the 3D macroporous PPy gels (PPGs). Serving as cathode materials for Na-ion batteries, the resulting 3D macroporous PPGs exhibit a high Na-ion storage capacity up to 106 mAh g-1 at 80 mA g-1, satisfactory rate capability and excellent cycling stability with a capacity retention of about 95% even after 200 cycles at a high rate of 150 mA g-1.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 3D; conducting polymers; macroporous; nanosheets; self-assembly